Thursday
May 23, 2013

# Homework Help: algebra

Posted by mema on Thursday, June 9, 2011 at 8:47pm.

solving the equation (x+4)(x-4)=9 Eric stated that the solution would be x+4=9>x=5 or (x-4)=9=>x=13
However one of these solution fails to work when subsituted back to the original equation. Why?olve and explain the reasoning. Can someone please help me?

No one has answered this question yet.

Related Questions

intermediate algebra - in solving the equation (x+4)(x-4)=9 eric stated the ...
Algebra - In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
algebra - 1. In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
math - In solving the equation (x + 4)(x – 7) = -18, Eric stated that the ...
algbera - In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
South - In solving the equation (x + 1)(x – 2) = 54, Eric stated that the ...
algebra - in solving the equation (x +2)(x - 2) = 32 eric stated the solution to...
Math - I don't understand how to solve this problem: In solving the equation...
Math - In solving the eqaution(x+4)(x-4),Eric stated thatthe solution would be x...
Intermediate Algebra - solve equation (x+1)(x-2)=54 Eric stated that the ...